1966
DOI: 10.1111/j.1464-410x.1966.tb09681.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Rupture of the Bladder

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
3

Year Published

1972
1972
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
7
0
3
Order By: Relevance
“…Spontaneous intraperitoneal rupture of the urinary bladder has been reported as a late complication of radiation therapy for cervical cancer [1]. Additional causes are distension resulting from outlet obstruction, alcohol intoxication, or a neurogenic bladder [2]. Bladder rupture can also occur due to malignant tumours, inflammatory lesions, diverticuli, calculi and following enterocystoplasty.…”
mentioning
confidence: 99%
“…Spontaneous intraperitoneal rupture of the urinary bladder has been reported as a late complication of radiation therapy for cervical cancer [1]. Additional causes are distension resulting from outlet obstruction, alcohol intoxication, or a neurogenic bladder [2]. Bladder rupture can also occur due to malignant tumours, inflammatory lesions, diverticuli, calculi and following enterocystoplasty.…”
mentioning
confidence: 99%
“…Until 1986, the only case of SRUB with a background of pelvic irradiation in the English-language literature was reported by Airman and Horsburgh in 1966 [7]. In 1986, Schein et al reported a case of SRUB in a 68 year old woman who had adjuvant radiotherapy following hysterectomy for cervical cancer 24 years before presentation [3].…”
Section: Discussionmentioning
confidence: 99%
“…Evans stellte 1976 eine Literaturübersicht von insgesamt 84 Fällen vor (6). Die Diagnosestellung erfolgt dabei häufig aufgrund der Symptomarmut verzögert (1,2,6). Bei dem vorgestellten Fall handelt es sich um einen Patienten, bei dem in einem Zeitraum von 13 Jahren insgesamt 8 Blasenspontanrupturen aufgetreten sind.…”
Section: Introductionunclassified
“…Zystoskopisch kann eine Blasenruptur -wie auch von uns einmal -als Divertikel fehlgedeutet werden (2). Der klassische Test der Bestimmung eines Fehlvolumens bei gleichzeitiger Blaseninstillation und Aspiration ist nicht immer eindeutig, beispielsweise im Falle einer ausreichend großen Perforationsstelle ohne Ventileffekt (1,2).…”
Section: Introductionunclassified